Perbedaan Keterampilan Berpikir Kritis melalui Model Pembelajaran Group Discovery Learning (GDL) Ditinjau dari Kemampuan Akademik Siswa - Perdana, Williamsyah Putra; Santosa, Slamet; Probosari, Riezky Maya (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2022)
Critical thinking skills include the ability to reason, analyze, make decisions, assess, explain, and self-regulate. This study was to determine the effect of Group Discovery Learning (GDL) on students' critical thinking skills in terms of academic abilities. This was a quasi-experimental research design using a post-test only with a non-equivalent control group design. The population was students of class X MIPA SMA Negeri 1 Sukoharjo. The subjects were taken using simple random sampling which met the normality and homogeneity tests. The sample was class X MIPA 5 as the control class and X MIPA 2 as the experimental class. Data were collected using essay tests, documentation, and observation. The hypothesis was tested with two-way ANOVA followed by the LSD test. The results show that: (1). Students' critical thinking skills were affected by the group discovery learning model. (2). There is a significant difference between students' academic abilities on critical thinking skills between control and experiment classes. These results can be used for further research in building active and innovative learning models and strategies